Voltage stability studies of wind turbine - Ei, Theingi Win (2011)
The voltage stability and ride-through capability of wind turbines is determined by the corresponding parameters and control policy of the wind turbines. The short-circuit failures in the transmission system can result in the acceleration of the wind turbines, which will absorb a significant amount of the reactive power from the power grid. In this case, voltage stability may not be maintained and the wind turbines will be disconnected from the grid by the protective devices. However the system operator requires that the system voltage can be maintained after a short circuit failure without the disconnection of the wind turbines with the transmission system. Therefore some reactive power compensation devices such as Statcom and synchronous compensators are used to supply reactive power in the contingency states when the grid voltage drops. The capability of maintaining the voltage stability can also be improved by carefully selecting generator parameters and control policies. In this project, the voltage stability of wind power system and redundancy of the reactive power compensation devices will be studied.